Integration of ESD-Based Education (Education for Sustainable Development) in the Science Curriculum - Utamirohmahsari; Khoa, Nguyen Minh; Santos, Maria Isabel (Saba Jaya Publisher, 2025)
Education for Sustainable Development (ESD) plays a pivotal role in addressing global challenges such as climate change, environmental degradation, and social inequality. The integration of ESD into science curricula is essential as science education provides the foundation for understanding natural phenomena and the relationship between humans and the environment. This paper explores the significance of incorporating ESD into science education in Indonesia, highlighting its potential to raise environmental awareness and foster sustainable behaviors from an early age. Despite its global recognition, the implementation of ESD in Indonesia faces several challenges, including the preparedness of educators, limited resources, and a lack of conceptual understanding of ESD. Effective strategies such as teacher training, development of sustainability-based teaching materials, and collaboration between schools, communities, and the private sector are crucial for overcoming these obstacles. Furthermore, adopting interdisciplinary and project-based learning approaches can enhance critical thinking and problem-solving skills, which are essential for addressing sustainability issues. The successful integration of ESD in science education is expected to produce a generation of students who are not only knowledgeable about sustainability but also actively contribute to achieving the Sustainable Development Goals (SDGs) by 2030. Through this approach, ESD becomes a transformative tool that shapes students' character as responsible agents of change, fostering a sustainable future.